2001
DOI: 10.1093/molehr/7.7.633
|View full text |Cite
|
Sign up to set email alerts
|

Anti-SLIP1-reactive proteins exist on human spermatozoa and are involved in zona pellucida binding

Abstract: Sulpholipid immobilizing protein 1 (SLIP1) is an evolutionarily conserved 68 kDa plasma membrane protein, present selectively in germ cells. We have previously shown that mouse sperm SLIP1 is involved in sperm-zona pellucida (ZP) binding. In this report, we extended our study to the human system. Immunoblotting demonstrated that anti-SLIP1-reactive proteins (mol. wt 68 and 48 kDa) could be extracted from human spermatozoa by an ATP-containing solution, a result that is consistent with observations in other spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 59 publications
2
15
0
Order By: Relevance
“…Consistent with proposed roles in cumulus dispersion and sperm-ZP interaction (Sabeur et al, 1997;Rattanachaiyanont et al, 2001;Tantibhedhyangkul et al, 2002), the proteins were co-localized within the peri-acrosomal region of the sperm head. Interestingly, the regulated alteration in the surface expression of both of these proteins does not occur until the latter stages of capacitation.…”
Section: Discussionsupporting
confidence: 84%
“…Consistent with proposed roles in cumulus dispersion and sperm-ZP interaction (Sabeur et al, 1997;Rattanachaiyanont et al, 2001;Tantibhedhyangkul et al, 2002), the proteins were co-localized within the peri-acrosomal region of the sperm head. Interestingly, the regulated alteration in the surface expression of both of these proteins does not occur until the latter stages of capacitation.…”
Section: Discussionsupporting
confidence: 84%
“…ASA in the remaining media was further purified using Q-sepharose resin and the total protein obtained and NCS desulfation activity was measured (after QS). Sperm arylsulfatase A and zona pellucida involved in sperm-ZP interaction and purified ASA binds to both intact and solubilized ZP (Rattanachaiyanont et al 2001, Carmona et al 2002a, Tantibhedhyangkul et al 2002, Wu et al 2007. In this report, we provided evidence that ASA was also present in the mouse AC and on the inner acrosomal membrane (Fig.…”
Section: Discussionmentioning
confidence: 59%
“…We have previously shown that sperm surface arylsulfatase A (ASA, EC 3.1.6.8) is involved in ZP binding in mice, pigs, and humans, and purified ASA can bind to intact or solubilized ZP directly (Rattanachaiyanont et al 2001, Carmona et al 2002a, Tantibhedhyangkul et al 2002. Nonetheless, the identity of the ZP glycoproteins to which ASA binds was not known, and this was one specific aim of the current research study.…”
Section: Introductionmentioning
confidence: 95%
“…This argument, however, appears to be at odds with the relatively high degree of cross-species conversation recorded among the known sperm-ZP receptors. 112,[126][127][128][129][130] Nonetheless, recent data regarding the role of the sperm protein, zonadhesin, promises to improve our understanding of the mechanisms behind the speciesspecific nature of sperm-ZP binding. 131 In this context, it has been shown that targeted deletion of zonadhesin leads to the production of mouse spermatozoa that bind promiscuously to the ZP of several divergent species.…”
Section: Structure Function and Biochemistry Of The Zpmentioning
confidence: 99%